Respuesta :

iametn

it would be multiplying i just got it right on my test.

Answer:

After substituting We multiply 5 with 9.

Step-by-step explanation:

Given Expression 5 + ( 9x - 3 ) ÷ 2

To evaluate this for x = 5, we have following steps

Step 1: Substitute value of x in expression

5 + ( 9 × 5 - 3 ) ÷ 2

Step 2: We Solve multiplication in bracket than complitly simplify the bracket

⇒ 5 + ( 45 - 3 ) ÷ 2

⇒ 5 + ( 42 ) ÷ 2

Step 3: Now we Divide 42 by 2

⇒ 5 + 21

Step 4: Add the no to get the answer

⇒ 26

Therefore, After substituting We multiply 5 with 9.